Digital Comic Media Design Using Canva to Improve Elementary School Students’ Reading Comprehension Skills - Utami, Monita; Martha, Alfroki; Ismira , Ismira (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The low literacy level among Indonesian students remains a pressing issue, as reflected in the country's 2022 PISA reading score of 359, down from 371 in 2018. This decline indicates a lack of reading interest, negatively impacting students’ academic performance. Specific Context: Observations and interviews at SD IT Mutiara Padang revealed that students exhibit low enthusiasm for reading, and instruction relies solely on conventional textbooks without engaging media. Knowledge Gap: An initial assessment showed that out of 25 students, only 5 achieved minimum reading comprehension competency, underscoring the urgent need for improved instructional tools. Objective: This study aims to develop and evaluate a digital comic medium to enhance the reading comprehension of grade IV elementary students. Results: The digital comic achieved a validity score of 95.4% (very valid), teacher practicality score of 90.83%, and student practicality score of 92.2% (both very practical). Its effectiveness yielded an N-Gain Score of 0.8052 (high) and an N-Gain percentage of 80.52% (effective). Novelty: The study introduces a technology-integrated learning medium accessible via digital and print formats. Implications: Digital comics can significantly improve reading comprehension skills and support teachers in delivering engaging classroom instruction. Highlights: Enhances reading comprehension using engaging digital media. Proven valid, practical, and effective in classroom application. Bridges the gap in student literacy with technology-based tools. Keywords: Digital Comics, Reading Comprehension, Elementary Education, Canva Media, Learning Innovation